DESCRIPTION OF DIFFERENT METHODS PREPARATION OF ROOT CANAL AND THEIR OBTURATION - Geranin, S.I. (World of Medicine and Biology, 2013)
During last years endodontic treatment are improve. Appearance new instruments and technologist of preparation root canals and their obturation. The choice of system for preparation root canal still to be discutable. Our own studies allow to draw the following comclusion. Used for preparation of root canal machine fails «Mtwo» and «Pro taper» are most effected.
Keywords: endodont; sealer; preparation root canal; fails; tooth slice